Investigation on the properties of acrylic emulsion polymer based ordinary portland cement concrete reinforced with hooked steel fiber - Dayang Siti Hazimmah, Ali (2015)
Polymer modified cement-based materials and fiber reinforced cementitious composites are both widely used in civil engineering applications. Both show great advantages, especially in repair and rehabilitation. The work reported here, however, deals with polymer modified fiber reinforced cement based composites (PM-FRC) that is, combined used of fibers and polymers in the same system. This paper reports the quantitative study of all the three additives each taken with three settings, namely, steel fiber (1.0%, 1.5% and 2.0%), acrylic emulsion polymer (1.0%, 2.5% and 4.0%) and silica fume (5.0%, 6.0% and 8.0%). The other two control variables were chosen as water-cement ratio (0.42, 0.50 and 0.60) and aging (3, 7 and 28 days). In this study, steel fiber reinforced polymer modified concrete (SFRPMC) was produced with the addition of acrylic emulsion polymer (<4%) into steel fiber reinforced concrete which enhance the workability, strength and thermal properties. The unique properties of steel fiber qualify it to be the best option as reinforcement in acrylic polymer cement composite. However, uniform dispersion is the biggest challenge in generating a composite with an optimum performance. Hence, acrylic emulsion polymer and silica fume with different percentages was used to improve the quality of steel fiber reinforced concrete. In this study, we have used a comprehensive approach known as Design of Experimental (DoE) which had been applied efficiently from the material formulation and processing stage until the material characterization. Through verification experiment, the compressive strength had increased by as much as 59% compared to control concrete specimen. To optimize other mechanical properties such as flexural strength, splitting tensile strength and modulus of elasticity, the L9 array method was used. Variant analysis and average analysis were then used to get the optimum formulation and through the X-ray diffraction analysis, the dispersion of acrylic polymer is slightly improved when combined with steel fiber reinforced concrete. From morphology observation, the dispersion of steel fiber with acrylic polymer addition showed a better uniformed dispersion in SFRPMC. Through thermal analysis, optimum specimen was proven to own good thermal stability than the other specimens. Steel fiber reinforced acrylic emulsion polymer modified concrete (SFRPMC) were produced based on the significant parameters suggested by Taguchi Analysis that was performed earlier. SFRPMC had improved the dispersion of steel fiber and acrylic polymer in matrix composite due to the presence of a few functional groups of elements from different materials, as observed through the morphology examination through SEMEDX analysis. Synergistic effect between the fibers and the polymer were observed in most of the composites as long as suitable polymer dosages were used. It is concluded that a high performance composites with 2.5% acrylic emulsion polymer, 8% silica fume, 1.5% steel fiber and water-cement ratio 0.50 at 28 days curing could be a promising material for both structural and repair purposes